2014
DOI: 10.1186/1471-2407-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol of a randomized controlled trial comparing Mindfulness-Based Stress Reduction with treatment as usual in reducing psychological distress in patients with lung cancer and their partners: the MILON study

Abstract: BackgroundLung cancer is the leading cause of cancer death worldwide and characterized by a poor prognosis. It has a major impact on the psychological wellbeing of patients and their partners. Recently, it has been shown that Mindfulness-Based Stress Reduction (MBSR) is effective in reducing anxiety and depressive symptoms in cancer patients. The generalization of these results is limited since most participants were female patients with breast cancer. Moreover, only one study examined the effectiveness of MBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 69 publications
0
20
0
3
Order By: Relevance
“…Second, our study is one of the few mindfulness intervention studies that also included patients' informal caregivers (Birnie, Garland, & Carlson, 2010; Schellekens et al, 2014; Schellekens et al, 2017; van den Hurk, Schellekens, Molema, Speckens, & van der Drift, 2015). As the number of individuals living with cancer increases, from 14 million in 2012 to a projected 18 million by 2022, the number of informal caregivers will grow in parallel (de Moor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Second, our study is one of the few mindfulness intervention studies that also included patients' informal caregivers (Birnie, Garland, & Carlson, 2010; Schellekens et al, 2014; Schellekens et al, 2017; van den Hurk, Schellekens, Molema, Speckens, & van der Drift, 2015). As the number of individuals living with cancer increases, from 14 million in 2012 to a projected 18 million by 2022, the number of informal caregivers will grow in parallel (de Moor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[27] This reflects the fast-growing number of studies that are conducted on the cost-effectiveness or cost-utility of psychosocial care. In addition, several protocol papers of currently ongoing studies were identified,[9454647484950] which will provide new evidence on the cost-effectiveness or cost-utility of psychosocial care in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Following CONSORT guidelines, we conducted a multicentre, parallel‐group, RCT comparing CAU + MBSR with CAU. The trial protocol has been published previously and received approval by the local medical ethics committee (CMO Arnhem‐Nijmegen, 2011‐519).…”
Section: Methodsmentioning
confidence: 99%
“…Participants received teachings on stress and grief and were invited to share their experiences. For more details, see study protocol . Three formally trained MBSR teachers fulfilling the advanced criteria of the Center for Mindfulness of the University of Massachusetts Medical School ran 9 MBSR groups in total with on average 9 participants per group (consisting of both study participants and patients with other cancer types).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation